Buckling of composite cylindrical shells fabricated using thin-ply under axial compression - HUANG Chun-fang; XIAO Jia-yu; HUANG Zhan-hong; ZHANG Jian-wei; JU Su; JIANG Da-zhi (工程科学学报)
Carbon-fiber reinforced polymer (CFRP) composites possess high specific stiffness and strength and have been widely used as structural materials in aerospace and aircraft engineering. In many practical applications, such as wing skin, loading condition is a complexity of tension, bending, and torsion. Therefore, fabricating CFRP composite laminates of multiple-angled plies is necessary to achieve balanced mechanical properties and meet the loading requirements under different working conditions. However, considering the size and weight limitations, designing a quasi-isotropic laminate with standard ply thickness (0.125 mm) is difficult. The recently developed spread-tow technique has provided a promising strategy to fabricate composite laminates of thin and light plies for the production of thinner and lighter laminates and structures and improvement of mechanical performance. Laminates fabricated using thin plies exhibit much higher strength in tension, compression, and impact as compared with standard-ply laminates because of the associated positive size effects. In the thin-walled structure, buckling stability is the primary factor determining the mechanical performance. In this study, composite cylindrical shells with different ply thickness (0.125, 0.055, and 0.020 mm) were fabricated via cross-ply and balanced stacking using the spread-tow technique, and their buckling behaviors under axial compression were studied. The experimental results show that with decreasing ply thickness, the critical buckling loads of composite cylindrical shells with cross-ply and balanced stacking under axial compression increase, whereas the buckling mode of composite cylindrical shells remains constant. Mechanical analysis indicates that the bending stiffness variation and interlaminar shear stress distribution play a key role in increasing the critical buckling load of the composite cylindrical shells, and the application of thin plies effectively improves the local buckling performance of the thin-walled composite structures.